"If you don't speak from the heart, the young mob aren't going to listen at all": An invitation for youth mental health services to engage in new ways of working. Issue 6 (9th July 2019) - Wright, Michael; Culbong, Tiana; Crisp, Nikayla; Biedermann, Britta; Lin, Ashleigh
Abstract: Aim: Aboriginal and Torres Strait Islander young people are more likely to experience mental health issues or end their life by suicide than non‐Aboriginal youth, but are less likely to access mental health services for support. Systemic change is required if mainstream youth mental health services are to be relevant and culturally secure for Aboriginal and Torres Strait Islander young people. Methods: Building Bridges (2017‐2019) is a three‐year participatory action research project being conducted in partnership with the Nyoongar community and three mainstream youth mental health services in Perth, Western Australia. The project involves Nyoongar Elders and Aboriginal and Torres Strait Islander young people working directly with senior management and key staff of youth mental health services to co‐design, implement and evaluate a framework for systems change. The aim of the project is to increase Aboriginal and Torres Strait Islander young people's engagement with services and improve mental health outcomes for young people and their families. Results: This paper outlines the engagement process that underpinned the first phase of the project. Our research methods are premised by an investment in establishing safe spaces for the Elders, young people and service staff to engage in open, honest dialogue. We present two key activities that illustrate this process of building trust and deepening understanding, namely: spending time "On Country" and engaging in a "storying" process. Conclusions: Building Bridges demonstrates the centrality of trusting relationships for systemic change and the way in which meaningful engagement is at the core of both the process and the outcome.